Biaya Imbangan Eksternalitas Pabrik Tahu di Kecamatan Jogoroto Kabupaten Jombang - Purbowo Purbowo; Siti Aisyatul Masruroh; Septi Ambar Indraningtia Sukma; Yessita Puspaningrum (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
This study aims to analyze the externality offset costs generated by tofu factories in Jogoroto District, Jombang Regency. Externalities are negative impacts resulting from production activities, which are not fully borne by producers but experienced by the surrounding community. This research uses quantitative methods to identify the type and magnitude of externalities, as well as to estimate the offset costs needed to curtail these negative impacts. The results showed that 87% have no problem with road noise, 86% are quite disturbed by engine noise, 88% of dust and air are not much and not disturbing and 86% feel the water is quite clean and normal. The negative externalities caused by the existence of a tofu factory in Jogoroto sub-district, Jombang regency are greater than the positive externalities provided by the tofu company with a total externality of Rp. -6,662,350,000. Policy recommendations to the Jombang regency government are to require factories to install effective wastewater treatment plants so that the wastewater discharged meets environmental quality standards and to conduct routine inspections and monitoring of water quality around the factory to ensure compliance with standards. Recommendations for collaboration between academics and the government in implementing filter and scrubber technology innovations as technologies that can minimize gas and particle emissions into the air.